OPTIMASI FORMULA TABLET HISAP EKSTRAK KULIT AKAR SENGGUGU (Clerodendrum serratum (L.) Moon.) SEBAGAI SEDIAAN OBAT PENGENCER LENDIR (MUKOLITIK) DENGAN KOMBINASI BAHAN PENGISI LAKTOSA – SORBITOL - Wahyono Wahyono; Luthfia Hanifah Kurniati; TN Saifullah Sulaiman (Faculty of Pharmacy, Universitas Gadjah Mada, 2015)
Senggugu root bark has mucolytic activity and has been used empirically, so it needs to be formulated as lozengeswhich can be used practically and comfortable for the patients. Senggugu root bark powder was extracted by maceration using aethanol 70%. Lozenges was optimized using lactose-sorbitol filler mix through three formulas, formula A ( 100% lactose), formula B (100% sorbitol), formula C (50% lactose-50% sorbitol). Lozenges was made by wet granulation method. The optimum formula was obtained from theresults of physical granul test and lozenges using SLD, and analyzed by its granul flow, hardness, dissolution time, and taste responsiveness, and also qualitative and quantitative analysis. The results show that lactose-sorbitol filler mix can increase hardness and taste responsiveness, decrease granul flow and dissolution time. The oprimum formula from this research is 100% sorbitol:0% lactose.